Influence of Philosophy in Elementary Education: A Study of E-9 Countries with special reference to Bangladesh, Pakistan, China, Indonesia and India - Koyel Palit (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2021)
Philosophy is the quest for truth and knowledge. Education is the means to strive at the path to seek knowledge. Education system of every country is guided by the philosophical thought of that country. Philosophy shapes the aims of the education system. Philosophy has direct rendering on curriculum, method of teaching, the role of teacher and learners. Elementary education is an important part of the education system of a country. The aim of this study is to find the influence of philosophy in elementary education of E-9 Countries. The formation of E-9 Countries has special significance in respect of elementary education. The researcher will try to describe the different schools of thought in E- 9 countries, specifically in India, Bangladesh, Pakistan, China and Indonesia. These schools of philosophy have effectively shaped the prevailing education system, mainly elementary education. This is a qualitative study based on document based logical analysis.